Vortex-Induced Vibrations on Cross Sections in Tandem Arrangement - Corriols, Abraham Sanchez; Morgenthal, Guido (Structural engineering international : journal of the International Association for Bridge and Structural Engineering (IABSE), 2014)
The progressive increase in the construction of long-span bridges in recent years has led to an increasingly detailed study of the aeroelastic effects observed for structural components such as decks, towers and cables. The greater flexibility due to larger spans and optimized cross sections result in critical wind speeds below the design wind speed and would have therefore a certain probability of occurrence during the service life. Such critical wind speeds should be increased by introducing some modification on the cross section geometry. Cables for suspension and cable-stayed bridges are subject to vibrations caused by galloping or gust effects, though these typically occur at high wind speeds. Flutter instability is driven by a fundamental vertical and torsional mode coupling at very high wind speeds. On the contrary, vortex-induced vibrations (VIV) are associated with a single vibration mode and are characteristic of a lower wind speed range. Vortex shedding causes amplitude-limited oscillations, as VIV is not aeroelastic instability. However, it can pose a danger to the structural integrity of the deck or discomfort to users, which would require the temporary bridge closure. Towers of cable-stayed and suspension bridges can also suffer this type of aeroelastic phenomenon. This paper examines the VIV phenomena on towers and decks in tandem configuration by computational fluid dynamic (CFD) methods and experimental wind tunnel tests. This paper specifically discusses the influence of the gap that separates the two main sections and the presence of obstacles, as bracing elements, that affect the fluid-structure interaction and thus their aerodynamic properties. The choice of a proper geometry in the design stage can avoid such low-wind speed vibrations on sections in tandem arrangement.